Temperature Acclimation of the Picoalga Ostreococcus tauri Triggers Early Fatty-Acid Variations and Involves a Plastidial ω3-Desaturase - Degraeve-Guilbault, Charlotte; Pankasem, Nattiwong; Gueirrero, Maurean; Lemoigne, Cécile; Domergue, Frédéric; Kotajima, Tomonori; Suzuki, Iwane; Joubès, Jérôme; Corellou, Florence (Frontiers in Plant Science, 2021)
Alteration of fatty-acid unsaturation is a universal response to temperature changes. Marine microalgae display the largest diversity of polyunsaturated fatty-acid whose content varies according to temperature. The physiological relevance and the molecular mechanisms underlying these changes have been however poorly investigated. The ancestral green picoalga Ostreococcus tauri displays original lipidic features that combines polyunsaturated fatty-acids (PUFA) from two distinctive microalgal phyla (Chlorophyceae, Chromista kingdom). In this study, optimized conditions were implemented to unveil early fatty-acid and desaturase transcriptional variations regulations upon chilling and warming. We further functionally characterized the O. tauri ω3-desaturase which is closely related to ω3-desaturases from Chromista species. Our results show that the overall omega-3 to omega-6 ratio is swiftly and reversibly regulated by temperature variations. The amount of the peculiar 18:5 fatty-acid and temperature are highly and inversely correlated pinpointing the importance of 18:5 temperature-dependent variations across kingdoms. Chilling rapidly and sustainably up-regulated most desaturase genes. Desaturases involved in the regulation of the C18-PUFA pool as well as the Δ5-desaturase appear to be major transcriptional targets. The only ω3-desaturase candidate, related to ω3-desaturases from Chromista species, is localized at chloroplasts in N. benthamiana and efficiently performs ω3-desaturation of C18-PUFA in Synechocystis PCC6803. Overexpression in the native host further unveils a broad impact on plastidial and non plastidial glycerolipids illustrated by the alteration of ω3/ω6 ratio in C16-PUFA and VLC-PUFA pools. Global glycerolipid features of the overexpressor recall those of chilling acclimated cells. The growth of O. tauri overexpressing the ω3-desaturase or the most active plastidial Δ6-desaturase remains however similar to control lines independently of temperature.